Effects of Communication Style on Competence Evaluations of Soccer Referees: Procedural Versus Relational Framing. (June 2023) - Burgers, Christian; van Biemen, Tammie; van Eeghen, Ruben; Mann, David L.
Good communication skills are important for soccer referees, but it remains unclear what exactly constitutes good referee communication. In this article, we focus on the role of verbal framing by soccer referees by contrasting the effects of procedural frames (focusing on rules and regulations) and relational frames (focusing on relational aspects) on perceptions of referee competence. We conducted an experiment ( N = 97) in which soccer referees used either procedural or relational frames to communicate about different types of in-game situations (yellow card and offside) to players. Results demonstrate that spectator perceptions of impartiality and confidence did not differ depending on the type of frame used. However, relational (vs. procedural) frames did increase spectator perceptions of respectfulness and communication skills. Soccer referees are recommended to use relational over procedural frames when communicating to players during a match.